« Micro lieux » appropriés sur le territoire du cercle familial - Gilles Henry (Sociétés et Jeunesses en Difficulté)
This paper focuses on the fact that a minority of young boys, aged 13 to 25, make use of « micro territories » close to their familie’s lodgings. It is based on an empirical research in the departement of Moselle. Methodology used is « symbolic interactionnism ».The research data shows that, thanks to this process, youngsters gain a sort of control or property which will then be materialized by territorial signs (or markages) : empty beer bottles, cigarette butts, tags. These « micro territories » host informal but nevertheless social relations for different groups which develop daily during a few months or sometimes several years. The phenomenon is stronger in social housing areas where they become locus for experiencing interactive relations, for resting, between « cosmos and chaos ». The author argues that these territories are a passage between the inside, private arena and the outside, public sphere, thus enabling a dynamic where internal and external social interactions emerge, where territorialization and deterritorialization operate depending on.